Coming to Know More Through and From Writing. (October 2016) - Prain, Vaughan; Hand, Brian
Over the past 20 years, claims about how and why student writing can serve learning have changed markedly. This has been partly due to new technologies displacing writing as a predominant resource for learning, prompting new sense-making practices and shifts in how these changes are theorized. Learners now routinely collaborate to generate, manipulate, analyze, and share images in many subject areas, where multimodal and multimedia resources are expected to motivate learners, enact new learning processes and outcomes, and display this cross-modal learning. These new practices have prompted revisions to how writing is understood and used as a tool for learning in an increasingly multimodal, highly digitized world. In reviewing this literature, we claim that there are strong evidence-based reasons for viewing writing as a central but not sole resource for learning. Our case draws on both past and current research on writing as an epistemological tool. In presenting this case, we draw primarily on our professional background in science education research, acknowledging its distinctive take on the use of writing for learning. However, we think our general case also holds for other disciplinary areas.